Corporate social responsibility initiatives and consumer satisfaction in an internet-based company: a mediating role of communication in the social media - Xiangzhou, Hua; Mohd Hasan, Nurul Ain; De Costa, Feroz; Abdullah, Zulhamri (Human Resource Management Academic Research Society, 2022)
In the era of brand economy, maintaining a good brand relationship between companies and consumers is the key for enhancing brand competitiveness and also reputations. By fulfilling corporate social responsibility (CSR), companies promote consumers' sensory and cognitive perception of their brands and products, and thus improve brand relationships and enhance consumers' satisfaction to their brands. Based on social media platforms, this study constructs a model of CSR and consumer satisfaction from the perspective of consumers for research by adopting Carroll's (1991) pyramid theory of CSR as the theoretical basis to classify the independent variable CSR into four dimensions: philanthropic responsibilities, ethical responsibilities, legal responsibilities and economic responsibilities. The dependent variable is consumer satisfaction. The social media CSR communication was used as a mediating variable, on which the research model was developed, and the scale and questionnaire were designed. Finally, an empirical study was conducted to verify the model and hypotheses and to analyze the relationship between the variables. Results indicated CSR as having a positive effect on consumer satisfaction and CSR communication in social media can play a mediating role in the research model. Accordingly, it can be concluded that companies can promote consumer satisfaction through social responsibility. Findings suggest that organisations can enhance consumer satisfaction by fulfilling philanthropic responsibilities, ethical responsibilities, legal responsibilities, economic responsibilities to enhance consumer satisfaction with the brand; and CSR communication through social media can promote consumer awareness of the brand, thus further enhancing consumer satisfaction towards the brand.